Enhancing Vocabulary in English Learning through Songs in Senior High School - Utami, Millen Rahmanisha; Taridi, Muhammad; Fadillah, Nisaul (Faculty of Social Science, Universitas Negeri Padang, 2025)
This study aims to improve students' English vocabulary mastery through song-based learning activities at SMAN 12 Merangin. The research method used is Classroom Action Research (CAR) with a qualitative approach. This study was conducted for two cycles. The research subjects were 30 students of class X of SMA Negeri 12 Merangin. The results of the study indicate that the application of song-based learning in English subjects has proven significant in improving students' English vocabulary mastery. This is evidenced by the data of an increase of 83.3% from the initial 66.7% after the application of the song method for 2 cycles of 4 meetings with a duration of 2x45 minutes each meeting. In cycle 1, the highest score was 95 and the lowest was 25, while the highest score in cycle 2 was 100 and the lowest was 50. The increase in the average score from cycle 1 to cycle 2 started from 76.7 to 87.3. This shows that, although the application of songs in English learning as an effort to improve English vocabulary mastery is effective, there are several factors that influence the results. Factors such as motivation, interest, active involvement of students during the learning process, as well as external factors such as the availability of learning media devices such as sound systems. However, the application of this learning method not only improves English vocabulary mastery, but also encourages student activity and interest in learning due to the application of songs in the learning process, thereby creating a more comfortable learning atmosphere, especially for students with an auditory learning style.